INVESTIGATING THE EFFECT OF CURCUMIN SUPPLEMENT CONSUMPTION ON SYSTEMATIC INFLAMMATION IN HEMODIALYSIS PATIENTS: Life Sciences-Biochemistry - MARYAM HAJINEZHAD KABODAN; AKRAM KOOSHKI; MOSTAFA RAD; YASER TABARRAIE; FARZANEH SHARIFIPOUR (International Journal of Life Science and Pharma Research, 2022)
Patients with Chronic Renal Failure (CRF) are exposed to extremely high risk for cardiovascular disease compared with others, so that at the initial stages of CRF, the incidence of cardiovascular diseases is higher than the progress of the disease toward the last stage of failure. Therefore, the present study aimed to investigate the effect of curcumin on serum lipid profile and systematic inflammation in hemodialysis patients. In this study, clinical practice was performed on 64 hemodialysis patients in Mashhad’s hospitals. Sampling in this study was based on random assignment method in the form of permuted block randomization. After gathering information, they were coded and transferred to the computer and after ensuring the accuracy of data, they were analyzed by SPSS 16 and chi-square test, fisher test, t-test, and Kolmogorov-Smirnov test. According to the analyses, the results of hypotheses testing showed that curcumin supplement consumption does not decrease the concentration of triglyceride, cholesterol, LDL of hemodialysis patients, and CRP. Also, the results of this study showed that curcumin supplement only has a slight effect on decreased cholesterol concentration, LDL of serum, and CRP in hemodialysis patients.